High NRF2 expression controls endoplasmic reticulum stress induced apoptosis in multiple myeloma. (1st January 2018) - Sun, Yu; Abdul Aziz, Amina; Bowles, Kristian; Rushworth, Stuart
Abstract: Multiple myeloma (MM) is an incurable disease characterized by clonal plasma cell proliferation. The stress response transcription factor Nuclear factor erythroid 2 [NF-E2]-related factor 2 (NRF2) is known to be activated in MM in response to proteasome inhibitors (PI). Here, we hypothesize that the transcription factor NRF2 whose physiological role is to protect cells from reactive oxygen species via the regulation of drug metabolism and antioxidant gene plays an important role in MM cells survival and proliferation. We report for the first time that NRF2 is constitutively activated in circa 50% of MM primary samples and all MM cell lines. Moreover, genetic inhibition of constitutively expressed NRF2 reduced MM cell viability. We confirm that PI induced further expression of NRF2 in MM cell lines and primary MM. Furthermore, genetic inhibition of NRF2 of PI treated MM cells increased ER-stress through the regulation of CCAAT-enhancer-binding protein homologous protein (CHOP). Finally, inhibition of NRF2 in combination with PI treatment significantly increased apoptosis in MM cells. Here we identify NRF2 as a key regulator of MM survival in treatment naive and PI treated cells. Highlights: We report for the first time that NRF2 is constitutively activated in circa 50% of MM primary samples. Proteasome inhibition induces further activation of NRF2 in primary MM. Inhibition of NRF2 in combination with PI treatment significantly increased apoptosis in primary MM.